Dipeptidyl peptidase 4 – An important digestive peptidase in Tenebrio molitor larvae. (September 2016) - Tereshchenkova, Valeriia F.; Goptar, Irina A.; Kulemzina, Irina A.; Zhuzhikov, Dmitry P.; Serebryakova, Marina V.; Belozersky, Mikhail A.; Dunaevsky, Yakov E.; Oppert, Brenda; Filippova, Irina Yu; Elpidina, Elena N.
Abstract: Dipeptidyl peptidase 4 (DPP 4) is a proline specific serine peptidase that plays an important role in different regulatory processes in mammals. In this report, we isolated and characterized a unique secreted digestive DPP 4 from the anterior midgut of a stored product pest, Tenebrio molitor larvae (TmDPP 4), with a biological function different than that of the well-studied mammalian DPP 4. The sequence of the purified enzyme was confirmed by mass-spectrometry, and was identical to the translated RNA sequence found in a gut EST database. The purified peptidase was characterized according to its localization in the midgut, and substrate specificity and inhibitor sensitivity were compared with those of human recombinant DPP 4 (rhDPP 4). The T . molitor enzyme was localized mainly in the anterior midgut of the larvae, and 81% of the activity was found in the fraction of soluble gut contents, while human DPP 4 is a membrane enzyme. TmDPP 4 was stable in the pH range 5.0–9.0, with an optimum activity at pH 7.9, similar to human DPP 4. Only specific inhibitors of serine peptidases, diisopropyl fluorophosphate and phenylmethylsulfonyl fluoride, suppressed TmDPP 4 activity, and the specific dipeptidyl peptidase inhibitor vildagliptin was most potent. The highest rate of TmDPP 4 hydrolysis was found for the synthetic substrate Arg-Pro-pNA, while Ala-Pro-pNA was a better substrate for rhDPP 4. Related to its function in the insect midgut, TmDPP 4 efficiently hydrolyzed the wheat storage proteins gliadins, which are major dietary proteins of T . molitor . Graphical abstract: Predicted three-dimensional structure of Tenebrio molitor dipeptidyl peptidase 4 – an insect enzyme with digestive function. Highlights: A proline specific serine peptidase, dipeptidyl peptidase 4, was found in the midgut of the yellow mealworm. The insect enzyme is specifically adapted for efficient digestion of wheat storage proteins. Localization and function of the insect enzyme are distinct from its mammalian counterpart.